FACTORS OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS A MODERATING VARIABLE AT PT.INCASI RAYA PADANG - Nia Nadilla (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to determine the factors of leadership style and work motivation as employee performance with the work environment as a moderating variable at PT Incasi Raya Padang. This method uses total sampling in which all populations are sampled with a total population and sample of 55 employees, from the sample who filled out the questionnaire as many as 55 employees. The analysis methods used in this study are Outer Model, Average Variance Extracted (AVE), Reliability Assessment, and Inner Model Testing (Structural Model) using Smart PLS 3.0. Based on the results showed that leadership style has a positive and insignificant effect on employee performance at PT. Incasi Raya Padang, work motivation has a positive and significant effect on employee performance at PT. Incasi Raya Padang, leadership style has a positive and significant effect on employee performance moderated by the work environment, work motivation has a positive and significant effect on employee performance moderated by the work environment